PEMANFAATAN MEDIA KOMIK STRIP TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI TEKS EKSPLANASI PADA SISWA KELAS V SD NEGERI LAMSAYUEN ACEH BESAR - Prety Mahareta; Aida Fitri; Hasniyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of students' critical thinking skills in learning explanatory texts. Students experienced difficulties in identifying facts, understanding cause-and-effect relationships, generating alternative solutions, and drawing conclusions from the information they obtained. Therefore, an engaging learning medium that suits the characteristics of elementary school students is needed, one of which is comic strips. This study aimed to describe students' learning activities during the use of comic strip media, examine the utilization of comic strip media in fostering students' critical thinking skills, and describe the results of students' critical thinking skills tests on explanatory text material in the fifth grade of SD Negeri Lamsayuen, Aceh Besar. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of 24 fifth-grade students of SD Negeri Lamsayuen, Aceh Besar. Data were collected through classroom observations and written tests developed based on critical thinking indicators, namely identifying facts, generating alternatives, understanding cause-and-effect relationships, and drawing conclusions. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings revealed that the use of comic strip media increased students' active participation during the learning process. Students showed greater enthusiasm for learning, demonstrated a better understanding of explanatory texts, and were able to identify important information and cause-and-effect relationships presented in the learning materials. The results of the critical thinking skills test indicated an average score of 87%, which falls into the very high category. Therefore, comic strip media can be effectively utilized to support students' critical thinking skills in learning explanatory texts while creating a more engaging, interactive, meaningful, and participatory learning environment for elementary school students.